Study on structural dynamic response of offshore wind turbine under floating ice load - Xin Guan; Hua Yu; Ying Yuan; Dechen Kong; Bo Liu; Hao Tang (Scientific Reports)
Abstract The structural dynamic characteristics of offshore wind turbines are directly related to the operational safety and equipment reliability of these turbines in service. However, due to the complex working conditions, a single load analysis fails to accurately reflect the structural dynamic characteristics during actual operation. In this study, we focus on the 5 MW offshore wind turbines and establish a three-dimensional turbulent flow field model at sea using the Kaimal wind speed spectrum. Additionally, we incorporate the Kärnä ice force spectrum to develop a mathematical model for floating ice. By combining multiple working conditions through permutation and combination techniques, we replicate the actual operating environment of offshore wind turbines. Leveraging OpenFAST’s open computing capabilities and EDEM’s discrete element analysis method, we investigate the dynamic response characteristics of wind turbines under separate and coupled effects of wind load, wave load, and ice load across different offshore working conditions. Our findings indicate that under coupling effects from wind-wave-ice loads, lateral and fore-aft displacement at the tower top as well as lateral and fore-aft bending moment at the tower foundation are greater compared to individual loads. However, cumulative fatigue damage caused by coupling loads on wind turbines is less than that resulting from individual loads.